Incrementality in Planning of Speech During Speaking and Reading Aloud: Evidence from Eye-Tracking - Ganushchak, Lesya Y.; Chen, Yiya (Frontiers in Psychology, 2016)
Speaking is an incremental process where planning and articulation interleave. While incrementality has been studied in reading and online speech production separately, it has not been directly compared within one investigation. This study set out to compare the extent of planning incrementality in online sentence formulation versus reading aloud and how discourse context may constrain the planning scope of utterance preparation differently in these two modes of speech planning. Two eye-tracking experiments are reported: participants either described pictures of transitive events (Experiment 1) or read aloud the written descriptions of those events (Experiment 2). In both experiments, the information status of an object character was manipulated in the discourse preceding each picture or sentence. In the Literal condition, participants heard a story where object character was literally mentioned (e.g., fly). In the No Mention condition, stories did not literally mention nor prime the object character depicted on the picture or written in the sentence. The target response was expected to have the same structure and content in all conditions (The frog catches the fly). During naming, the results showed shorter speech onset latencies in the Literal condition than in the No Mention condition. However, no significant differences in gaze durations were found. In contrast, during reading, there were no significant differences in speech onset latencies but there were significantly longer gaze durations to the target picture/word in the Literal than in the No Mention condition. Our results shot that planning is more incremental during reading than during naming and that discourse context can be helpful during speaker but may hinder during reading aloud. Taken together our results suggest that on-line planning of response is affected by both linguistic and non-linguistic factors.